A Critical Analysis of the WAQ: The Development of a Korean Form. Issue 5 (October 2021) - Kang, Sudol
The current study aimed to develop a simplified version of the Korean Workaholism Scale (KOWS) by determining the reliability and validity of the Workaholism Analysis Questionnaire (WAQ) initially created by Aziz et al. The original scale of the WAQ was translated into Korean and then administered to 4, 242 working people from a broad range of economic sectors. The nation-wide sample was a representative one from the 17th wave Korean Labor and Income Panel Study in 2014. The main body comprises two steps. First, through an exploratory factor analysis (EFA) as well as a reliability analysis, along with content validity examination among experts, thirteen items from the original WAQ were eliminated. The EFA yielded a four-factor solution with four items established in compulsive dependency (CD), four in illusion of control (IC), four in endurance of conflicts (EC), and four in withdrawal symptoms (WS). This process provided a succinct and convenient measure of workaholism, the KOWS with 16 items. The reliability coefficient (α) of the new scale was .90, and the split-half reliability coefficient was .72. Secondly, confirmatory factor analysis (CFA) was performed by way of structural equation modeling to validate the new construct. This KOWS showed adequate convergent validity (AVE > .5), construct reliability (CR > .7), as well as discriminant validity (AVE > ρ 2 ). Between four subscales of the KOWS and affective commitment (AC) to organizations there proved meager correlation. In conclusion, the KOWS with 16-item psychometric properties is a valid and reliable tool to measure workaholism in South Korea.